2020
DOI: 10.1017/s1478951520000309
|View full text |Cite
|
Sign up to set email alerts
|

Dying concerns in young parents with advanced cancer (PWAC): A scoping review

Abstract: Background Advanced cancer in young parents (PWAC) can increase dying concerns, the fluctuating thoughts, or feelings, conscious, or unconscious, about an approaching death by a person facing a terminal illness or a family member coping with the impending death of a loved one. However, limited research has been conducted to identify dying concerns in an ill parent as the research has focused on older adults. Objective Our goal was to identify dying concerns that PWAC are expressing and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…In recent studies, PWACs of dependent children had concerns for their coparent that included concerns such as coping abilities and living as a single parent; the ability to emotionally and practically support all family members, including themselves; and concerns for the quality of parenting the children would receive in the event of their death. 6,[10][11][12][13][14] The most commonly used tool to measure concerns for the coparent from the ill parent's perspective was the Parental Concern Questionnaire (PCQ). 6,[10][11][12][13][14] The PCQ measures parenting concerns in patients with any stage of cancer who have dependent children on a 5-point ordinal scale and has 3 subscales measuring concerns about the emotional and practical impact of the illness on children and concerns about the coparent.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In recent studies, PWACs of dependent children had concerns for their coparent that included concerns such as coping abilities and living as a single parent; the ability to emotionally and practically support all family members, including themselves; and concerns for the quality of parenting the children would receive in the event of their death. 6,[10][11][12][13][14] The most commonly used tool to measure concerns for the coparent from the ill parent's perspective was the Parental Concern Questionnaire (PCQ). 6,[10][11][12][13][14] The PCQ measures parenting concerns in patients with any stage of cancer who have dependent children on a 5-point ordinal scale and has 3 subscales measuring concerns about the emotional and practical impact of the illness on children and concerns about the coparent.…”
mentioning
confidence: 99%
“…6 Dying concerns are defined as fluctuating thoughts or feelings that are conscious or unconscious about an accepted and approaching death that stem from a terminal diagnosis by the person facing the terminal illness or by a family member coping with the impending death of a loved one. [6][7][8][9] Extant literature has focused on the concerns of parenting while experiencing a terminal illness and the challenges the parents face, as well as the impact of advanced cancer on the children. 6 While the research lacks a comprehensive definition of dying concerns, a recent scoping review 6 found that dying concerns include the concerns of parents with advanced cancer (PWACs) for their children, concerns for their coparent, and personal concerns.…”
mentioning
confidence: 99%
See 3 more Smart Citations